Oceanology the true account of the voyage of the Nautilus by Zoticus de Lesseps, 1863 - Hawkins, Emily; Wood, A. J. 1960-.; Anderson, Wayne (Surrey, [England] Templar, 2009)
Purports to be the journal of Zoticus de Lesseps, written on an ill-fated 1863 voyage accompanying Captain Nemo to explore the mysteries of the deep sea.
Presented as a scrapbook with liftable flaps, stuffed envelopes, and other attached or detached items. Front cover includes a porthole cut-out over a 3-D picture of an octopus on the title page.
Suitable for age 6 and up.
Keywords: Underwater exploration -- Juvenile fiction; Submarines (Ships) -- Juvenile fiction; Nemo, Captain (Fictitious character) -- Juvenile fiction; Submarine captains -- Juvenile fiction; Atlantis (Legendary place) -- Juvenile fiction; Sea stories; Adventure stories; Toy and movable books -- Specimens; Diaries -- Juvenile fiction